Efektivitas Senam Osteoartrhitis Dalam Stabilisasi Indeks Massa Tubuh Di Masyarakat - Yuniartika, Wachidah; Mutiah, Siti (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2021)
Osteoarthritis is a disorder of the aging process. One of the risk factors for osteoarthritis is obesity orexcessive body mass index (BMI). Weight loss in people with osteoarthritis can be done by doing exercises.Objective To determine the effectiveness of osteoarthritis exercise in stabilizing body mass index inosteoarthritis sufferers. This type of quantitative research uses a pre-experimental design one-group pretestposttest design. Research Sites in the Village of Makam Haji Sukoharjo, Central Java Province, Indonesia,were conducted from January to February 2020 with 32 respondents, using the purposive sampling method.The inclusion criteria were 20-60 years old, did not experience pain attacks, the patient did not have otherdiseases. The calculation of BMI uses measurements of weight and height. Analyzed using Paired T-Test. Theresults were obtained at the pretest BMI the majority were overweight as much as 24 (75%), at the posttestthe majority BMI was normal as much as 28 (87.5%), the results of the paired sample test with a P-value of0.001. Conclusion: There is an effect of giving osteoarthritis exercise on body mass index. The average BMIafter exercise is normal.